Accounting and Finance Innovations - Alsharari, Nizar M. (IntechOpen, 2021)
The world is currently experiencing the advent of new information technologies with dynamic changes, which can be considered as one of the greatest business threats today. Accordingly, international business and academia have claimed to be working towards developing innovations in accounting and finance that are useful for all stakeholders. The recent accounting and finance scholarship has moved forward toward new innovations that advance professional practice. This book introduces and discusses new innovations in accounting and finance, including management accounting, blockchain, E-business models, data analytics, artificial intelligence, cryptocurrency, bitcoin, digital assets, and associated risks. It also sheds light on how and why accounting and finance innovations have changed over time. This book will help practitioners and academics develop and introduce new accounting and finance tools and concepts. It is also a useful resource for those working in the accounting and finance fields.